Financial development and economic growth: evidence from Lesotho, 1981 - 2022 - Nteso, Ntsane (School of Economics, 2026)
This research explores the significant impact of financial development on Lesotho's economic growth over the period 1981–2022, employing a methodology inspired by the endogenous growth model proposed by King and Levine (1993). The study utilizes the This research explores the significant impact of financial development on Lesotho's economic growth over the period 1981–2022, employing a methodology inspired by the endogenous growth model proposed by King and Levine (1993). The study utilizes the Autoregressive Distributed Lag (ARDL) approach to cointegration, specifically applying the ARDL bounds-testing methodology. To capture the multifaceted aspects of financial development, four distinct proxy variables are used: ratio of liquid liabilities to GDP, private credit by deposit money banks and other financial institutions as a percentage of GDP, deposit money bank assets to deposit money bank assets and central bank assets and domestic credit to private sector as a percentage of GDP divided by domestic credit to private sector as a percentage of GDP plus credit to government and state-owned enterprises as a percentage of GDP. Initially, this study explores the influence of financial development on economic growth using all four proxy variables. Interestingly, only one variable - the ratio of liquid liabilities to GDP - emerges as statistically significant. However, its impact is negative in both the short and long run. Consistent with King and Levine's (1993) suggestions about the channels through which financial development affects economic growth, this research further explores the impact of the ratio of liquid liabilities to GDP on two crucial growth components: total productivity growth and the accumulation of physical capital. The results present a convincing narrative, revealing that the log of ratio of liquid liabilities to GDP has a negative impact on Lesotho's growth while having no significant effect on either total factor productivity growth or physical capital accumulation. This paper contends that financial liberalization in a poorly regulated environment may have contributed to this outcome. Consequently, the evidence suggests that the country may not be fully leveraging the potential benefits of financial development to drive economic prosperity.(ARDL) approach to cointegration, specifically applying the ARDL bounds-testing methodology. To capture the multifaceted aspects of financial development, four distinct proxy variables are used: ratio of liquid liabilities to GDP, private credit by deposit money banks and other financial institutions as a percentage of GDP, deposit money bank assets to deposit money bank assets and central bank assets and domestic credit to private sector as a percentage of GDP divided by domestic credit to private sector as a percentage of GDP plus credit to government and state-owned enterprises as a percentage of GDP. Initially, this study explores the influence of financial development on economic growth using all four proxy variables. Interestingly, only one variable - the ratio of liquid liabilities to GDP - emerges as statistically significant. However, its impact is negative in both the short and long run. Consistent with King and Levine's (1993) suggestions about the channels through which financial development affects economic growth, this research further explores the impact of the ratio of liquid liabilities to GDP on two crucial growth components: total productivity growth and the accumulation of physical capital. The results present a convincing narrative, revealing that the log of ratio of liquid liabilities to GDP has a negative impact on Lesotho's growth while having no significant effect on either total factor productivity growth or physical capital accumulation. This paper contends that financial liberalization in a poorly regulated environment may have contributed to this outcome. Consequently, the evidence suggests that the country may not be fully leveraging the potential benefits of financial development to drive economic prosperity.